Exploring the progress and challenges of ultrasonic technology in environmental remediation - Ningqing Lv; Rongshan Wu; Ruonan Guo; Linlin Wu; Heng Zhang; Changsheng Guo; Jian Xu (Ultrasonics Sonochemistry)
Amidst escalating environmental pollution due to accelerated industrialization and urbanization, there is an acute demand for effective and sustainable environmental remediation strategies. Ultrasonic technology, recognized for its green and efficient characteristics, has gained significant prominence in mitigating environmental pollution in aquatic, soil, and atmospheric ecosystems. The review provides a comprehensive analysis of the role of ultrasonic treatment in wastewater treatment, air quality improvement, and soil remediation. We systematically evaluate existing research to assess the effectiveness of ultrasonic technology in degrading pollutants and its potential for large-scale deployment. The review also examines the challenges associated with ultrasonic remediation, including optimizing operational parameters, enhancing energy transfer efficiency, and understanding the unique degradation mechanisms for various pollutants. Furthermore, we discuss environmental and safety considerations, along with the economic implications related to equipment costs and energy consumption. This review aims to contribute to the advancement of ultrasonic technology in environmental remediation by presenting a forward-looking perspective, aligning with the goals of environmental protection and sustainable development.